Comparing the effectiveness of bivalent and monovalent COVID-19 vaccines against COVID-19 infection during the winter season of 2022-2023: a real-world retrospective observational matched cohort study in the Republic of Korea - Chae, Chungman; Kim, Ryu Kyung; Jang, Eun Jung; Shim, Ji Ae; Park, Eunkyung; Lee, Kil Hun; Hong, Sye Lim; Aziz, Asma Binte; Tadesse, Birkneh Tilahun; Marks, Florian; Tak, Sangwoo; Lee, Sangwon; et al. (International journal of infectious diseases, 2023)
Objectives - To compare the effectiveness of bivalent and monovalent COVID-19 vaccines throughout the 2022-2023 winter season based on real-world data. - Methods - This retrospective observational matched cohort study used the national vaccination program and a surveillance dataset from the Republic of Korea, and included adults aged >18 years who received bivalent or monovalent COVID-19 vaccines between October 11, 2022, and December 17, 2022. Cox proportional hazard models were used to estimate the hazard ratio for COVID-19 infection between the groups. - Results - We included 29,245 matched individuals in the bivalent and monovalent vaccine groups, respectively. The bivalent vaccine recipients showed 12.2% (95% confidence interval [CI] 6.5-17.7%) additional protection against COVID-19 infection compared with the monovalent vaccine recipients. The additional protection provided by bivalent vaccines was significantly higher among residents of long-term care facilities (39.4%, 95% CI 21.6-53.1%). Maximum additional protection was observed 3 to 4 months after completing the vaccination (17.6%, 95% CI 6.6-27.3%). - Conclusion - Bivalent COVID-19 vaccines showed significantly better protection against infection than monovalent vaccines among adults during the 2022-2023 winter season. Our results highlight that immunization programs with bivalent vaccines comprising recent variants can be an effective measure to prepare for seasonal COVID-19 circulation.
Online verfügbar: 11. August 2023, Artikelversion: 31. August 2023
Gesehen am 08.11.2023